Service-Oriented Computing - ICSOC 2008 Workshops ICSOC 2008, International Workshops, Sydney, Australia, December 1st, 2008. Revised Selected Papers. - Feuerlicht, George; Lamersdorf, Winfried (Programming and Software Engineering,, 2009)
This book constitutes the thoroughly refereed papers presented at five international workshops held in conjunction with the 6th International Conference on Service-Oriented Computing, ICSOC 2008, in Sydney, Australia, in December 2008. The volume contains 41 reviewed and improved papers presented at the 4th International Workshop on Engineering Service-Oriented Applications (WESOA 2008), the Second International Workshop on Web APIs and Services Mashups (Mashups 2008), the First International Workshop on Quality-of-Service Concerns in Service Oriented Architectures (QoSCSOA 2008), the First Workshop on Enabling Service Business Ecosystems (ESBE 2008), and the Third International Workshop on Trends in Enterprise Architecture Research (TEAR 2008). The papers offer a wide range of hot topics in service-oriented computing: management and analysis of SOA processes; development of mashups; QoS and trust models in service-oriented multi-agent systems; service ecosystems, service standardization, and evolutionary changes of Web services; governance aspects of SOA, enterprise models and architectures.